Sex, gender and emerging infectious disease surveillance: a leptospirosis case study - Yuzo Arima; Jozika Skufca (World Health Organization Regional Office for the Western Pacific, 2012)
Whatever the population, wherever the place, whenever the period, sex has been an essential demographic variable for surveillance. However, the distinction between "sex" and "gender" has not always been well understood or acknowledged by those of us engaged in public health surveillance. Sex refers to the biological and physiological factors that define males and females, while gender refers to socially constructed roles and attributes that a particular society considers appropriate for men and women. While both sex and gender factors contribute to reported surveillance data, their full contributions are often not recognized. When such data are then used to ascertain sex/gender differential in disease risk without caution, the complete picture behind the observed distribution may be missed or misinterpreted. Using leptospirosis as a case example, we describe the importance of interpreting surveillance data with a more gender-sensitive perspective, considering the various biological and social factors behind the reported numbers.